Buklet sebagai Media Pencegahan terhadap Kekerasan Seksual pada Anak-anak - Paramastri, Ira; Prawitasari, J. E.; Prabandari, Yayi Suryo; Ekowarni, Endang (UI Scholars Hub, 2011)
Kekerasan seksual pada anak (KSA) merupakan aktivitas seksual yang melibatkan anak-anak oleh orang yang lebih dewasa. Perbuatan ini mengakibatkan trauma, baik fisik, psikis, sosial, maupun perilaku. Fenomena ini tidak selalu terlaporkan mengingat keadaan, kesediaan atau keberanian korban untuk melaporkan, dukungan keluarga untuk mempertahankan laporan ke polisi, dan kepedulian berbagai pihak pada perlindungan anak. Demi melindungi anak maka diperlukan suatu strategi preventif untuk mengantisipasi meluasnya kasus tersebut. Media buklet diharapkan dapat menjadi salah satu bentuk media pendukung pencegahan terhadap KSA. Suatu studi dilakukan untuk menguji apakah media buklet dapat dipakai sebagai alat pencegahan KSA, khususnya bagi siswa sekolah dasar (SD). Metode studi yaitu deskriptif dengan subjek 4 orang ahli media. Analisis deskriptif digunakan untuk mengukur kelayakan media buklet melalui penilaian para ahli media tersebut. Hasilnya ditemukan bahwa warna, tipe huruf, ukuran huruf, kesesuaian antara gambar dan kata, maupun kalimat serta substansi materi yang terdapat dalam buklet yang diuji sudah sesuai untuk siswa, walau dengan beberapa saran untuk direvisi. Studi ini menyimpulkan bahwa medium buklet dapat diterapkan pada siswa SD sebagai alat pendukung pencegahan KSA. Child sexual abuse (CSA) is a sexual activity involving the children by the adults. The acts have caused physical, psychological, social, and behavior trauma as well. This phenomena was not always been recorded, due to circumstances and the courages of the victims and family to report to the police, as well as concern of various parties to protect the children. For the sake of child protection, a prevention strategy is needed to anticipate the cases spread out. Booklet is expected to be one of the supporting media for CSA prevention. A study was carried out to test the use of booklet as the prevention medium for the CSA, especially for the elementary school students. This is a descriptive method using 4 media experts as subject. Descriptive analysis was used to measure the booklet use through the media experts review. As result, this study found that colors, font type, font size, compatibility of pictures and words, and sentences, as well as materials are suited to the elementary school students, although there are some revisions needed. It can be concluded that booklet can be applied as preventive tool toward the CSA, particularly for the elementary school students. Child sexual abuse (CSA) is a sexual activity involving the children by the adults. The acts have caused physical, psychological, social, and behavior trauma as well. This phenomena was not always been recorded, due to circumstances and the courages of the victims and family to report to the police, as well as concern of various parties to protect the children. For the sake of child protection, a prevention strategy is needed to anticipate the cases spread out. Booklet is expected to be one of the supporting media for CSA prevention. A study was carried out to test the use of booklet as the prevention medium for the CSA, especially for the elementary school students. This is a descriptive method using 4 media experts as subject. Descriptive analysis was used to measure the booklet use through the media experts review. As result, this study found that colors, font type, font size, compatibility of pictures and words, and sentences, as well as materials are suited to the elementary school students, although there are some revisions needed. It can be concluded that booklet can be applied as preventive tool toward the CSA, particularly for the elementary school students.